Веси (VESI) magazine: presentation of the publication (Confluenţe Bibliologice, 2019)
In this article the authors presents an original magazine, which gives users beautiful opportunity to get acquainted with modern prose and poetry. Publishers have an attractive conception about edition. The magazine ,,ВЕСИ” is excellently illustrated. All authors are with speciﬁc mentality features and diﬀerent literary styles. Many of them come from Bălţi and another moldovan cities and villages.
Keywords: periodicals; collection of the USARB Scientiﬁc Library